Acculturation, Gender, Depression, and Cigarette Smoking Among U.S. Hispanic Youth: The Mediating Role of Perceived Discrimination - Lorenzo-Blanco, Elma I. (2011)
Hispanic youth are at risk for experiencing depressive symptoms and smoking cigarettes, and risk for depressive symptoms and cigarette use increase as Hispanic youth acculturate to U.S. culture. The mechanism by which acculturation leads to symptoms of depression and cigarette smoking is not well understood. The present study examined whether perceived discrimination explained the associations of acculturation with depressive symptoms and cigarette smoking among 1,124 Hispanic youth (54% female). Youth in Southern California completed surveys in 9th–11th grade. Separate analyses by gender showed that perceived discrimination explained the relationship between acculturation and depressive symptoms for girls only. There was also evidence that discrimination explained the relationship between acculturation and cigarette smoking among girls, but the effect was only marginally significant. Acculturation was associated with depressive symptoms and smoking among girls only. Perceived discrimination predicted depressive symptoms in both genders, and discrimination was positively associated with cigarette smoking for girls but not boys. These results support the notion that, although Hispanic boys and girls experience acculturation and discrimination, their mental health and smoking behaviors are differentially affected by these experiences. Moreover, the results indicate that acculturation, gender, and discrimination are important factors to consider when addressing Hispanic youth’s mental health and substance use behaviors.